Pengembangan Potensi Lokal Pesisir Dalam Pengelolaan Untuk Meningkatkan Pendapatan Ekonomi Masyarakat Studi Kasus Desa Lubuk Tukkobaru Tapanuli Tengah - Novitri, Dian; Nurizatunisa, Anzalna; Siregar, Padrie Payung; Irwansyah, Irwansyah (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2023)
This activity aims to take advantage of the natural resources of Lubuk Tukko Baru Village, namely fish which can be used as the main raw material for making a product such as shredded fish and can be used by residents as a product that can generate profits to meet their daily needs and increase income for help the economy. The method used is Analysis of Village Conditions and Potential and conducting counseling and conducting direct training with the surrounding community, especially mothers in Lubuk Tukko Baru Village. The results of the activity show that there is a positive response from the community in the Lubuk Tukko Baru Village area in counseling and After the fish floss making training, the community also knows the economic value of the practice of making fish floss and should be used as an additional source of income for the people of Lubuk Tukko Baru Village. Apart from offline marketing, online marketing is also very helpful and a solution to increase income. housewives in the Lubuk Tukko Baru Village area. executor of Community Service Program (KKN) at the State Islamic University of North Sumatra in Lubuk Tukko Baru Village, Pandan sub-district, Central Tapanuli Regency, Lubuk Tukko Baru Village Community Lack of knowledge in the utilization of Natural Resources (SDA) which are very abundant in their village but with the implementation of counseling and training on making shredded fish showed that the enthusiasm of the villagers who took part in the program was very good.